Effect of hydrogen peroxide treatment on the proteome profile of Musca domestica larvae / Tan Yong Hao - Tan, Yong Hao (2016)
The effects of acute treatment of hydrogen peroxide (LC50 = 21.52% (v/v)) on the expression of cytosolic and thiol proteins of housefly (Musca domestica) 3rd instar larvae were investigated. Using two dimensional gel electrophoresis, differential analysis was performed to identify protein with moderate (2 to 5 times) and high (more than 5 times) fold changes. In the total proteome, 17 spots and 23 spots were discovered to have moderate fold change respectively in control and treated samples. 3 different identified protein spots were shown increase in high fold change in both treated and non-treated larvae samples respectively. Qualitatively, there was presence of extra expression in 2 and 4 different protein spots in both control and treated samples respectively. The variation of expression of thiol proteins was also investigated by analyzing the purified thiol proteome upon acute peroxide treatment. 5 thiol proteins and 6 thiol proteins were found to have a moderate fold change in control and treated samples respectively. There were 2 different identified thiol protein spots increased at high fold changes in both treated and non-treated larvae samples. Our work has also shown that qualitatively, a significant presence of 4 protein spots in treated samples which were absent in the control samples. Protein spots with high fold changes were identified using LC-MS/MS based peptide mass fingerprinting and biomarkers related with important biological functions were identified including cytoskeleton (actin and tropomyosin), protein degradation (ubiquitin), odorant binding (PBP/GOBP family protein), energy metabolism (arginine kinase), anaerobic metabolism/gluconeogenesis/TCA cycle (Lactate/malate dehydrogenase), and glycolysis/gluconeogenesis (Fructose bisphosphate aldolase). Arginine kinase and fructose bisphosphate aldolase are high in abundance in thiol proteome profile, suggesting their high tolerance of cysteine residues under acute hydrogen peroxide induced oxidative stress.